PENERAPAN TEKNIK EMPTY CHAIR UNTUK MENINGKATKAN RASA KEPERCAYAAN DIRI SISWA SMP KORBAN BULLYING DI KOTA TERNATE - Rukmana Arahmin; Suryani Hi Umar; Mawardi Djamaludin; Widya Ali; Eka Deviyanti S. Djafar; Isti Saindra; Elfi Fatmona; Rahmadina Andi; Siti Naina Y. Daud; Risma Iswandi; Dwi Mahika Faradila; Iin Minisari Hi Sehe; Isabela Rainomina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bullying remains a serious problem in schools because it affects students' mental health, social relationships, and self-confidence. Data from UNESCO and BPS show high rates of bullying in Indonesia, including in North Maluku. Students who are victims of bullying tend to experience anxiety, low self-esteem, and difficulty socializing. To address this problem, one approach used is the empty chair technique, a Gestalt counseling method that helps students express their feelings and resolve intrapersonal conflicts, thereby increasing their self-confidence. This study aims to describe the application of the empty chair technique in students at junior high school Kota Ternate and determine its effectiveness in increasing the self-confidence of bullying victims. The study used a quantitative approach with a quasi-experimental nonequivalent control group design. The study population consisted of 48 eleventh-grade students, with a sample of 16 students selected through proportionate stratified random sampling. The data collection instrument was a self-confidence scale, while data analysis was performed using descriptive and inferential statistical techniques. The results showed a significant increase in students' self-confidence levels after receiving treatment through the empty chair technique. Bullying victims who participated in group counseling sessions showed positive changes, such as daring to express their opinions, being more optimistic, and being able to control themselves in social interactions. Thus, this study concluded that the empty chair technique is effective in helping bullying victims rebuild their self-confidence.